2021
DOI: 10.1111/jopr.13334
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Patient Specific Factors on Occlusal Forces Generated: Best Evidence Consensus Statement

Abstract: Purpose: The purpose of this Best Evidence Consensus Statement was to search the literature to determine if there is a relationship between patient specific factors and occlusal force. Materials and Methods: A literature review was conducted in the following databases: Evidence-Based Medicine Reviews (EBMR), Cochrane Database of Systematic Reviews, Embase, and Ovid MEDLINE(R) and Epub Ahead of Print. Articles on patient factors and occlusal force were compiled by using a combination of the key words: "bite for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 99 publications
(182 reference statements)
1
8
0
Order By: Relevance
“…Shinogaya et al (2001) reported a lower occlusal force and higher contact area between teeth in senior subjects compared to younger subjects [ 208 ]. Recent studies also present results in accordance [ 209 , 210 , 211 , 212 ]. Mechanical properties are also affected by the age of the specimen.…”
Section: Patient Dependent Factorssupporting
confidence: 78%
See 2 more Smart Citations
“…Shinogaya et al (2001) reported a lower occlusal force and higher contact area between teeth in senior subjects compared to younger subjects [ 208 ]. Recent studies also present results in accordance [ 209 , 210 , 211 , 212 ]. Mechanical properties are also affected by the age of the specimen.…”
Section: Patient Dependent Factorssupporting
confidence: 78%
“…Gender, as well, is a relevant characteristic towards the total occlusion force that can be exerted between teeth. The magnitude of the MBF is different between genders [ 211 ]. Braun et al (1996) studied the changes in MBF during growth in both male and female subjects from 6 to 20 years old, finding out that during growth, MBF increases in both males and females in a similar manner, but after puberty, male maximum bite forces increase at a greater great than females [ 215 ].…”
Section: Patient Dependent Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Turkistani et al have shown that Class III malocclusion subjects with decreased overjet and decreased overbite displayed higher bite force in the posterior teeth compared to other groups [ 14 ]. The spectrum of occlusal force differs widely among subjects linked to patient-specific factors such as age, gender, partial and full edentulism, existence of a maxillofacial defect, edentulous position, orthognathic profile, and vertical occlusal dimension magnitude [ 15 ]. Using a transducer occlusal force meter (GM10; Nagano Keiki, Tokyo, Japan), Al-Zarea [ 16 ] reported that the maximum occlusal bite force values on the dentate side are greater than those on the fixed partial denture side.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it should be acknowledged that participants were apparently aware of having a sophisticated and modern implant treatment modality, that could have made them satisfied with their dentures and this is in agreement with a study done (33) . Partial or complete prosthetic replacement of missing dentition is associated with reduced chewing efficiency and consequently decreased patient satisfaction (34) . The positioning of posterior teeth and the bite force are the most important factors affecting the efficiency of the masticatory system (35) .…”
Section: Discussionmentioning
confidence: 99%